Управлінський аспект розвитку інновацій сільськогосподарських підприємств - Гончаренко, Оксана Володимирівна; Honcharenko, Oksana; Тимощук, Василь Васильович; Tymoshchuk, Vasyl (Причорноморський науково-дослідний інститут економіки та інновацій і Сумський державний педагогічний університет імені А.С. Макаренка, 2024)
Стаття присвячена узагальненню тенденцій сучасного розвитку агропромислового виробництва й обґрунтуванню елементів та складових інституціонального забезпечення розвитку інновацій сільськогосподарських підприємств. Акцентовано, що інноваційний розвиток є беззаперечним стратегічним вектором розвитку як національної економіки так і її аграрної сфери. Визначено, що реалізація інноваційного розвитку обумовлює запровадження управлінського інструментарію, орієнтованого на поширення агроінновацій, сучасних технологій, цифровізації бізнес-моделей і логістики, що сприятиме зростанню показників продуктивності та ефективності діяльності сільськогосподарських підприємств. Обґрунтовано, що в короткостроковому періоді інституціональний управлінський вплив має бути спрямованим на трансформацію структури агропромислового виробництва, запровадження заходів для відходу від вузькоспеціалізованої моделі аграрного виробництва та експорту. В довгостроковому періоді управлінський інструментарій має орієнтуватися на інноваційну модернізацію агропромислового виробництва та базуватися на поширенні агроінновацій сільськогосподарськими підприємствами. The article is devoted to the generalization of trends in the modern development of agro-industrial production and the substantiation of the elements and components of institutional support for the development of innovations in agricultural enterprises. It is emphasized that innovative development is an indisputable strategic vector for the development of both the national economy and its agrarian sphere. It was determined that the implementation of innovative development requires the introduction of management tools aimed at the spread of agricultural innovations, modern technologies, digitalization of business models and logistics, which will contribute to the growth of productivity and efficiency indicators of agricultural enterprises. It was established that the state, as a key management institution in the implementation of innovative transformations, is able to initiate impulses towards the development of a favorable business environment and the formation of an investment climate; to ensure the protection of intellectual property and the attraction of foreign investments; to form formal norms that regulate the improvement of the quality of agricultural science and education; to initiate mechanisms for stimulating the incomes of employees of agrarian enterprises and the development of rural areas; to modernize the system of communication, transport and logistics, infrastructure development. The implementation of innovative priorities requires the formation of institutional support for the development of innovations in agricultural enterprises, through which managerial impulses can be introduced to initiate the managed innovative modernization of agro-industrial production. Prospects for the implementation of the toolkit of the program-targeted approach for the implementation of the tasks of innovative development of agro-industrial production have been studied. It was established that its application in national realities requires specification of strategic priorities, resource filling and institutional systematicity. It is justified that in the short term, the institutional management influence should be aimed at the transformation of the structure of agro-industrial production, the introduction of measures to move away from the highly specialized model of agricultural production and export. In the long term, the management toolkit should focus on the innovative modernization of agro-industrial production and be based on the spread of agro-innovations by agricultural enterprises
Management aspect of innovation development of agricultural enterprises
Keywords: агроінновація; agricultural innovation; зелена економіка; green economy; сільськогосподарські підприємства; agricultural enterprises; інноваційний розвиток; innovative development; інноваційна модернізація; innovative modernization; програмно-цільовий підхід; program-target approach; управління розвитком; development management